Pengaruh Citra Merek, Varian Produk dan Harga Terhadap Keputusan Pembelian Smartphone Oppo - Radika Anggraini; Baidowi Abdhie; Herlan Djunaidi (Jurnal Kompetitif, 2024)
Abstract  This research was conducted at Tridinanti University, Faculty of Economics and Business, Management study program which aims to find out how much influence brand image, product variants and price have on OPPO smartphone purchasing decisions (Case Study of Undergraduate Students at the Faculty of Management Economics Semester 7, Tridinanti University). The sample in this study was 70 people. The analysis technique used is multiple linear regression which is processed using the Statistical Product and Service Solution (SPSS) computer program version 25.0. The results of this research produce a multiple linear regression equation model Y = 2,231 + 0.283 X1 + 0.237 X2 + 549 X3 + e. The constant has a positive value of 2.231, meaning it shows a unidirectional influence between the independent variable and the dependent variable. A Sig F value of 0.00 < 0.05 shows that brand image, product variants and price simultaneously have a significant influence on the decision to purchase an OPPO smartphone (Case Study of Undergraduate Students at the 7th Semester Faculty of Management Economics, Tridinanti University). In the partial T test, the Image variable has a positive and significant effect with a sig value of 0.007 < 0.05. The second variable: Product variant has a positive and significant effect on the decision to purchase an OPPO smartphone (Case Study of Undergraduate Students, Faculty of Management Economics Semester 7, Tridinanti University), with a sig value of 0.043 > 0.05 and Price has a positive and significant effect on the decision to purchase an OPPO smartphone (Case Study of Students S1 Faculty of Management Economics Semester 7, Tridinanti University), with a score of 0.000 < 0.05. Abstrak : Penelitian ini dilakukan di Universitas Tridinanti, Fakultas Ekonomi dan Bisnis, Program studi manajemen yang bertujuan untuk mengetahui seberapa besar pengaruh citra merek, varian produk, dan harga terhadap keputusan pembelian smartphone OPPO (Studi Kasus Mahasiswa S1 Fakultas Ekonomi Manajemen Semester 7 Universitas Tridinanti). Sampel pada penelitian ini sebanyak 70 orang. Teknik analisis yang digunakan adalah regresi linier berganda yang diolah menggunakan bantuan program komputer Statistical Product and Service Solution (SPSS) varsi 25.0. Hasil penelitian ini menghasilkan model persamaan regresi linier berganda Y = 2.231 + 0,283 X1 + 0,237 X2 + 549 X3 + e. Konstanta memiliki nilai positif 2.231, artinya menunjukkan pengaruh yang searah antara variabel independen dan variabel dependen. Nilai Sig F 0,00 < 0,05 menunjukkan Citra merek, Varian produk, dan Harga secara simultan berpengaruh signifikan terhadap Keputusan pembelian smartphone OPPO (Studi Kasus Mahasiswa S1 Fakultas Ekonomi Manajemen Semester 7 Universitas Tridinanti). Pada Uji T secara parsial variabel Citra merek berpengaruh positif dan signifikan dengan nilai sig sebesar 0,007 < 0,05. Variabel kedua Varian produk berpengaruh positif dan signifikan terhadap Keputusan pembelian smartphone OPPO (Studi Kasus Mahasiswa S1 Fakultas Ekonomi Manajemen Semester 7 Universitas Tridinanti), dengan nilai sig 0,043 > 0,05 dan Harga berpengaruh positif dan signifikan terhadap Keputusan pembelian smartphone OPPO (Studi Kasus Mahasiswa S1 Fakultas Ekonomi Manajemen Semester 7 Universitas Tridinanti), dengan nilai 0,000 < 0,05.